Pendidikan Tinggi sebagai Arena Transformasi Pembangunan Wilayah BARSELA; Antara Peluang dan Tantangan - Akmal Saputra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2018)
Abstract This article based on the reality of development in West Aceh. West Aceh is currently being intensively undertaken development on various sectors, one of them in the education sector. This article aims to examine how development opportunities and challenges are in the education sector, why is development in the education sector important?, also to examine what and how the role of academics in development of education sector ?. Research method used in this article is literature review. The approach is Improvement Approach and Tranformation Approach. The result of the research shows that the role of academics is considered very important to advance education in Barsela region, especially West Aceh. The role of academic can be shown through the implementation of tri darma of higher education; education, research and community service. Academics have an important role to change the mindset of society interested in continuing higher education. In additio, academics and government must synergize in conducting development programs, especially in education. Education is the spearhead of development, higher education as an arena of development transformation has a big chance, but has many challenges, one of the public interest towards universities is still considered less and people still have the mindset that universities need is expensive. This mindset has become a habitus in some people who are in the middle to lower class, whereas society is the subject of development. Keywords: Higher Education, Development Transformation, Opportunities and Challenges